Improving the Effectiveness of TalentCorp’s Initiatives : Assessment of Returning Expert Program and Residence Pass-Talent - World Bank (World Bank, Washington, DC, 2016)
The information contained in this summary report reflects the analysis and assessment that have been undertaken beginning January 2013 mainly to assess the effectiveness of TalentCorp’s efforts to attract and retain global talent through its Returning Expert Program (REP) and Residence Pass-Talent (RP-T). The initial research included various activities aimed at improving the client’s ability to meet its mandate. The main activities completed were as follows: (1) creation of a platform to identify and monitor local labor market conditions and human capital/talent needs; (2) creation of a profile of the Malaysian diaspora living abroad; (3) creation and implementation of two surveys, both surveys focused on gauging the attractiveness of working in Malaysia and were targeted at the Malaysian diaspora and foreign talent living in Malaysia; (4) an impact evaluation of the REP, which aims to facilitate highly skilled members of the Malaysian professionals abroad back to Malaysia; and (5) an assessment of the effectiveness of the RP-T Program, which aims to retain foreign talent in Malaysia. In both the impact evaluation and the assessment, the main questions investigated are whether these programs effectively attract/retain talent.